2015
DOI: 10.1016/j.jadohealth.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Large Doses of Vitamin D Fail to Increase 25-Hydroxyvitamin D Levels or to Alter Cardiovascular Risk Factors in Obese Adolescents: A Pilot Study

Abstract: Supplementation with vitamin D at 150,000 IU every 3 months failed to increase serum 25OHD or alter inflammatory markers and lipids in overweight and obese youth. Further studies are needed to establish the dose of vitamin D required to increase 25OHD and determine potential effects on metabolic risk factors in obese teens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…We have previously shown that 50 000 IU vitamin D weekly and 1 000 mg calcium daily cosupplementation for 8 weeks among overweight and vitamin D-deficient patients with PCOS decreased serum hs-CRP levels [11]. Supplementation with vitamin D did not alter inflammatory markers among overweight and obese youth for 24 weeks [29] and among subjects with pre-diabetes and hypovitaminosis D for 12 months [30]. In addition, Kim et al [31] have shown that serum hs-CRP levels were positively associated with vitamin K deficiency in young adult women.…”
mentioning
confidence: 85%
“…We have previously shown that 50 000 IU vitamin D weekly and 1 000 mg calcium daily cosupplementation for 8 weeks among overweight and vitamin D-deficient patients with PCOS decreased serum hs-CRP levels [11]. Supplementation with vitamin D did not alter inflammatory markers among overweight and obese youth for 24 weeks [29] and among subjects with pre-diabetes and hypovitaminosis D for 12 months [30]. In addition, Kim et al [31] have shown that serum hs-CRP levels were positively associated with vitamin K deficiency in young adult women.…”
mentioning
confidence: 85%
“…Some, but not all, studies describe a similar association between 25(OH)D and inflammatory markers in HIV [17][18][19]. Increasing 25(OH)D levels through supplementation has a favourable effect on BMD [20] and cellular immune activation levels [21], though less evidence exists for other inflammatory markers associated with cardiovascular risk [22,23].…”
mentioning
confidence: 99%
“…Shah et al [4] carried out a trial relevant to this important area of research in this issue of the Journal of Adolescent Health. Previous investigation has proposed insufficient serum 25-hydroxyvitamin D (25OHD) to be a contributor to vascular complications in obese children, with evidence provided by Codoñer-Franch et al [3] including increased markers of oxidative stress, inflammation, and endothelial activation in that population.…”
mentioning
confidence: 99%